The Encyclopedia of Animal Biology - Alexander, R. McNeill (England Promotional Reprint Company, 1991)
Molecules - Cells - Feeding & digestion - Gas exchange & circulation - Senses - Co-ordination & control - Reproduction & development - Digestive systems in animals including ruminant herbivores - Human digestive system.
Include Index, Bibliography, Glossary and Illustration
Keywords: Physiology -- Zoology